Wartości niematerialne i prawne - bilansowe i podatkowe zasady odpisywania planowanej utraty wartości - Trzcińska, Dorota (Intangible Fixed Assets - Accounting and Fiscal Rules of Planned Depreciation, 2005)
This article presents accounting and fiscal rules connected with the depreciation of intangible fixed assets as exemplification of lower value. They are defined differently and there is also a difference in the area of methods of depreciating intangible fixed assets. That results in the necessity of having a detailed account. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 219-227